Leveraging Traditional Ecological Knowledge and Access to Nutrient-Rich Indigenous Foods to Help Achieve SDG 2: An Analysis of the Indigenous Foods of Sauria Paharias, a Vulnerable Tribal Community in Jharkhand, India - Ghosh-Jerath, Suparna; Kapoor, Ridhima; Singh, Archna; Downs, Shauna; Barman, Satabdi; Fanzo, Jessica (Frontiers in Nutrition, 2020)
Indigenous food systems of traditional communities are potentially sustainable, have nutrient rich food sources and can enhance dietary diversity. Sauria Paharias, are one of the particularly vulnerable tribal groups of Jharkhand India, who despite residing in rich biodiverse environment and possessing traditional ecological knowledge, lag behind various health and nutritional indicators. Our study explored their traditional ecological knowledge around indigenous foods (IFs), their routine consumption, access and nutritive values. A cross-sectional mixed methods study was carried out in 18 villages of Godda district, Jharkhand. Free list of all IFs known to the community was developed using focus group discussions. This was followed by enumerating commonly consumed as well as little or historically used IFs. Following the taxonomic classification of these foods, their nutritive values were searched in literature or food samples were analysed in accredited laboratories. Reasons for consumption and non-consumption of specific IFs were explored. The community was aware of a large number of IFs (n=193) but only 50% of these were routinely consumed. Rest were either little used or historically consumed. About 47.6% IFs (n=92) were identified using taxonomic classification; of which 87 IFs were classified based on their common names in secondary literature and five food items were collected, herbariums were prepared and identified. Nutritive values were documented for 84 IFs (this included both routinely consumed as well as little used); out of which 55 foods were found to have nutritive values in existing literature and 29 foods were analyzed in laboratory. Many of these IFs were rich in micronutrients like calcium, iron, zinc, folic acid, vitamin A and vitamin C. Common reasons for preferences or non-consumption of specific IFs included taste, availability, access seasonality, opportunity cost of access and processing time. Promoting adequate intake commonly accessed nutrient rich IFs and revival of little used IFs while addressing the causes of non-consumption and mainstreaming them into the daily diets could be an effective strategy to increase the intake of micronutrients. Policies focusing on incorporation of nutrient rich IFs into dietary diversification strategies and ongoing supplementary feeding programs can help address malnutrition in the community.